Correlation between elastic parameters and collagen fibre features in breast lesions. Issue 6 (June 2018) - Shi, X.-Q.; Li, J.; Qian, L.; Xue, X.; Li, J.; Wan, W.
Abstract : Aim: To correlate elastic parameters with collagen fibre shape and arrangement features in breast lesions. Materials and methods: Shear-wave elastography (SWE) was used to measure the stiffness of breast lesions in 54 patients before surgical removal. The value of stiffness was expressed as the mean and maximum elasticity (Emean and Emax). Lesions were sliced and stained with picric acid–sirius red to display the extracellular matrix (ECM) collagen fibre. The categories of the collagen fibres were based on the shape and arrangement features, i.e., category 0, wavy collagen fibres similar to normal breast tissue; category 1, taut parallel collagen fibres around tumour nests; category 2, straightened and aligned collagen fibres tending to be perpendicular to the tumour boundary; category 3, collagen fibre in a honeycomb arrangement. Bivariate correlation analysis was used to analyse the relationship between elastic parameters and collagen fibre category. Results: For all 54 lesions, the correlation coefficient between Emean and category was 0.693 ( p  < 0.001), and between Emax and category was 0.794 ( p  < 0.001). For 36 malignant lesions, the correlation coefficient between Emean and category was 0.658 ( p  < 0.001), and between Emax and category was 0.771 ( p  < 0.001). Conclusion: Emean and Emax of breast lesions evaluated by SWE were positively correlated with ECM collagen fibre shape and arrangement category. Changes of ECM collagen fibre shape and arrangement may account for the stiffness variations of breast lesions. Highlights: Category of collagen fibres shape and arrangement features in breast lesions was developed. The mean and maximum elasticity of breast lesions evaluated by SWE were positively correlated with the category of collagen fibre shape and arrangement. Changes of ECM collagen fibre shape and arrangement may account for the stiffness variations of breast lesions.